Dengue-Associated Acute ST-Elevation Myocardial Infarction: Navigating Anti-thrombotic Therapy in Severe Thrombocytopenia (Journal of Medicine, 2026)
Dengue fever is a mosquito-borne viral disease transmitted by Aedes mosquitoes particularly Aedes aegypti. There are 4 distinct serotypes (DEN1, DEN2, DEN3, and DEN4) causing dengue fever. The clinical manifestations of dengue fever are variable- fever, headache, body ache, retro-orbital pain, rash, & joint pain. It has a wide range of clinical manifestations, ranging from asymptomatic disease to a more complicated form -dengue hemorrhagic fever or dengue shock syndrome (DHF/DSS), which is characterized by increased vascular permeability, thrombocytopenia (platelets